Model Alat Monitoring Baku Mutu Air Bebasis Web Terkendali Mikrokontroler - Hidayatulloh, Rizqi; Bahar, Bahar (STMIK Banjarbaru, 2023)
Monitoring the quality of water quality standards using direct observation methods at the monitoring site is not effective. This research develops an automatic and real-time Quality Standards Monitoring System. The device design involves Potential Hydrogen (pH), Total Dissolved Solids (TDS), and temperature sensors controlled by a microcontroller. The sensors as system input are placed in water media which will be monitored for quality standards. These sensors read water parameters in real time. Data from sensor readings is processed by a microcontroller, then distributed via a global communication network to web-based or mobile-based application modules on gadget devices. Through this gadget terminal, users can monitor water quality standards in real time, thereby increasing the effectiveness of the process of monitoring water quality standards. System implementation can be carried out in various business fields, such as the land fisheries sector to monitor the condition of fish pond water, the agricultural sector to monitor hydroponic cooking media, and the facilities and infrastructure for processing clean water for household consumption.Key words: Water quality standards; Microcontroller; Hydrogen potential sensor; Total Dissolved Solids Sensor; Temperature sensorAbstrakPemantauan kualitas baku mutu air yang dilakukan dengan menggunakan metode observasi langsung ke tempat pemantauan tidak efektif. Penelitian ini mengembangkan Sistem Monitoring Baku Mutu secara otomatis dan realtime. Desain alat melibatkan sensor Potensial Hidrogen (pH), Total Dissolved Solids (TDS), dan suhu yang dikendalikan oleh mikrokontroler. Sensor-sensor sebagai input sistem diletakan pada media air yang akan dipantau baku mutunya. Sensor-sensor tersebut membaca parameter-parameter air secara realtime. Data Hasil pembacaan sensor diproses oleh mikrokontroler, kemudian didistribusikan melalui jaringan komunikasi global ke modul aplikasi berbasis web atau berbasis Mobile pada perangkat gadget. Melalui terminal gadget tersebut, pengguna dapat memantau baku mutu air secara realtime, sehingga dapat meningkatkan efektivitas proses pemantauan baku mutu air. Implementasi sistem dapat dilakukan pada berbagai bidang bisnis, seperti bidang perikanan darat untuk memantau keadaan air kolam ikan, bidang pertanian untuk memantau media tanam hidroponik, dan bidang sarana dan prasarana pengolahan air bersih untu konsumsi rumah tangga.